Comparative Analysis of Five Commercial RT-PCR Diagnostic Assay for Detection of Covid-19 - Hasanzadeh, Sepideh; Mehri, Ali; Hajebi Khaniki, Saeedeh; Azari, Behnam; Jangi, Mahbubeh; Ghazvivni, Kiarash; Amel Jamehdar, Saeid (International Journal of Coronaviruses, 2023)
SARS-CoV-2 real-time reverse-transcription PCR (rRT-PCR) is the most effective testing system available to combat COVID-19, given the absence of any specific treatment or vaccine. Moreover, numerous SARS-CoV-2 rRT-PCR kits have been approved under emergency-use-authorization (EUA) worldwide. In this article, we present a comparison of important performance features among five commercial RT-PCR assays. A total of consecutive nasopharyngeal (NPS) samples and oropharyngeal (OP) swabs were collected from 50 COVID-19 patients to analyze sensitivity and specificity. The results showed variations in sensitivity among all the RT-PCR kits examined. The Pishtaz teb assays demonstrated the highest positive percent agreement (PPA) of 95.2% (40/42), followed by Covitech (90.5% - 38/42), DaAn Gene (83.3% - 35/42), Sansure (66.66% - 28/42), and Power check of SARS- CoV-2 panel (64.3% - 27/42). Conversely, all five molecular assays demonstrated a negative percent agreement (NPA) of 100% (8/8). These findings provide a technical baseline for assessing the performance of five distinct commercial PCR assays for detecting SARS-CoV-2. They could prove practical and useful for laboratories seeking to purchase any of these assays for further clinical validation. Highlights ·Compared five COVID-19 RT-PCR kits approved and available by Iran Ministry of Health. ·Pishtaz teb's kit identified the highest number of positive clinical samples.
Keywords: Severe acute respiratory syndrome coronavirus; In vitro diagnostics; Coronavirus; SARS-CoV-2; Real Time RT-PCR.